2010
DOI: 10.1007/s11033-010-0284-y
|View full text |Cite
|
Sign up to set email alerts
|

DD genotype of ace gene I/D polymorphism is associated in a turkish study population with osteoarthritis

Abstract: This study was conducted in Turkish osteoarthritis patients to determine the frequency of I/D polymorphism genotypes of angiotensin converting enzyme gene, and to examine the role of this polymorphism in osteoarthritis development. Genomic DNA obtained from 200 persons (135 patients with osteoarthritis and 65 healthy controls) was used in the study. DNA was multiplied by polymerase chain reaction using I and D allele-specific primers. Polymerase chain reaction products were assessed with CCD camera by being ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 16 publications
2
21
0
Order By: Relevance
“…Control subjects were consecutively selected among people without personal and family history of OA. The clinical characteristics of patients with OA and controls were summarized in Table 1 [13].…”
Section: Study Populationmentioning
confidence: 99%
“…Control subjects were consecutively selected among people without personal and family history of OA. The clinical characteristics of patients with OA and controls were summarized in Table 1 [13].…”
Section: Study Populationmentioning
confidence: 99%
“…32,33 Up to now, several studies on the association between ACE I/D polymorphism and atopic disorders have been reported. [34][35][36] The mechanism underlying why the ACE I/D polymorphism affects susceptibility to atopic disorders is undetermined. There is ample evidence indicating that the ACE I/D polymorphism may modulate the expression of the ACE gene and the DD and D allele of the ACE gene which brings about higher plasma ACE levels and increased angiotensin II levels which are associated with many atopic disorders such as rheumatoid arthritis, asthma and nephrotic syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…A large difference has been reported in the usual circulation of ACE gene alleles in different populations. The frequency of D allele in normal Caucasians is 50-58%, but 35-39% in normal Chinese [20][21][22]. The renin-angiotensin system plays an key role in maintaining body fluid and sodium balance and has been involved in a many complex disorders [23][24][25].…”
Section: Ra Patient Characteristics N=200mentioning
confidence: 99%
“…Gunes, et al [32] also did not found any difference in ACE gene I/D polymorphism genotypes in hypertensive patients and healthy controls in the Turkis population. Bayram, et al [22] reported that DD homozygotes was found to be significantly higher in osteoarthritis than in healthy controls (DD) and D allele frequency and DD homozygosis were found to be significantly higher in polycystic ovary syndrome patients than in controls in the Turkish population. ACE gene also considered as a top candidate gene for cardiovascular studies as well [33].…”
Section: Ra Patient Characteristics N=200mentioning
confidence: 99%